2008
DOI: 10.1128/jcm.00770-08
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between Mycobacterial Interspersed Repetitive-Unit-Variable-Number Tandem-Repeat Typing and IS 6110 Restriction Fragment Length Polymorphism Genotyping for Analysis of Mycobacterium tuberculosis Beijing Strains in a Setting of High Incidence of Tuberculosis

Abstract: IS6110 restriction fragment length polymorphism (RFLP) genotyping is the most widely used genotyping method to study the epidemiology of Mycobacterium tuberculosis. However, due to the complexity of the IS6110 RFLP genotyping technique, and the interpretation of RFLP data, mycobacterial interspersed repetitive-unitvariable-number tandem-repeat (MIRU-VNTR) genotyping has been proposed as the new genotyping standard. This study aimed to determine the discriminatory power of different MIRU-VNTR locus combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 36 publications
6
60
1
Order By: Relevance
“…It has already been shown that 12-loci MIRU-VNTR typing was not sufficient to discriminate Beijing family strains (6,9). Similarly, Hanekom and colleagues reported that even 15-and 24-loci MIRU-VNTR typing has a reduced discriminatory power compared to IS6110 typing for strains of the Beijing lineage in Cape Town, South Africa, and that the inclusion of more variable loci might be necessary to reach the same level as that with IS6110 RFLP typing (7). As an exception, Shamputa et al found a similar discriminatory power of 24-loci MIRU-VNTR and IS6110 RFLP typing on Korean Beijing strains and suggested that 24-loci-based MIRU-VNTR typing is a likely suitable alternative to RFLP to differentiate clinical isolates in their setting dominated by Beijing strains (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has already been shown that 12-loci MIRU-VNTR typing was not sufficient to discriminate Beijing family strains (6,9). Similarly, Hanekom and colleagues reported that even 15-and 24-loci MIRU-VNTR typing has a reduced discriminatory power compared to IS6110 typing for strains of the Beijing lineage in Cape Town, South Africa, and that the inclusion of more variable loci might be necessary to reach the same level as that with IS6110 RFLP typing (7). As an exception, Shamputa et al found a similar discriminatory power of 24-loci MIRU-VNTR and IS6110 RFLP typing on Korean Beijing strains and suggested that 24-loci-based MIRU-VNTR typing is a likely suitable alternative to RFLP to differentiate clinical isolates in their setting dominated by Beijing strains (15).…”
Section: Discussionmentioning
confidence: 99%
“…In comparative populationbased evaluations, we and others found a similar if not slightly better performance of 15-or 24-loci MIRU-VNTR typing compared to IS6110 RFLP typing for discrimination of clinical isolates and detection of transmission chains in TB patient populations (13). Few subsequent studies compared MIRU-VNTR typing with the "gold standard" IS6110 RFLP typing, because the latter is rather laborious and more difficult to perform (6,7,15). The majority of the studies confirmed the initial finding that 24-loci MIRU typing can be used for MTBC genotyping with a similar performance as IS6110 typing, but some studies suggested a lower discriminatory power of 24-loci MIRU-VNTR typing in settings where Beijing strains are dominant (7,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar trends have been observed in other African countries where local genotypes tend to form a greater proportion of the circulating strains (Kallenius et al, 1999;Niobe-Eyangoh et al, 2004;Easterbrook et al, 2004;Chihota et al, 2007). In recent findings, a study showed that different strains of M. tuberculosis have adapted to specific human populations and such strains have a higher probability of transmission than others (Gagneux et al, 2006;Gagneux & Small, 2007;Hanekom et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings indicate that different strains of M. tuberculosis have adapted to specific human populations and such strains have a higher probability of transmission in these communities than others (Gagneux et al, 2006;Gagneux & Small, 2007;Hanekom et al, 2008). The Beijing family is thought to be hyper-virulent and to have high probability for developing drug resistance .…”
Section: Introductionmentioning
confidence: 99%